Design, Antioxidant Evaluation and in Silico Anticancer Profiling of Novel Quinoline Derivatives Targeting Apoptosis, Angiogenesis and Metastasis - Pradeepa Kumar C; B. T. Prabhakar; N. D. Satyanarayan; Rajeshwara Achur (The Bioscan, 2026)
Quinoline-based scaffolds continue to attract significant interest in anticancer drug discovery due to their structural versatility and broad spectrum of biological activities. In this study, five novel quinoline compounds (QCs) were synthesized and evaluated for their antioxidant and anticancer potential using in vitro assays and in silico approaches. Antioxidant activity was assessed using DPPH and ABTS radical scavenging assays, where all compounds exhibited concentration-dependent activity. At 500 µg/mL, QC-1 demonstrated the highest DPPH radical scavenging activity (69.88 ± 2.90%), while QC-2 showed the greatest ABTS scavenging activity (75.11 ± 2.40%). Molecular docking studies revealed strong binding affinities of all quinoline derivatives toward key cancer-related targets, including BAX, Bcl-2, p53, VEGF, MMP-2 and MMP-9, in comparison to the reference drug 5-fluorouracil. Furthermore, molecular dynamics simulation identified QC-4 as the most stable ligand–protein complex, highlighting its potential as a lead anticancer candidate. Notably, QC-3 exhibited the most favourable multi-target binding profile, suggesting its ability to modulate apoptosis, angiogenesis and metastasis pathways. Overall, the combined antioxidant and in silico findings indicate that quinoline derivatives, particularly QC-3 and QC-4, represent promising multifunctional scaffolds for further anticancer drug development. KEYWORDS Quinoline derivatives; Anticancer activity; Antioxidant activity; Molecular dynamics simulation; In silico studies